Effect of Ball Milling Parameters on Properties of Nano-Sized Tungsten Powder via Mechanochemical Processing - Feng Li; Guihang Zhang; Pengfei Zheng; Wei Qian; Yaxia Wei; Bingsheng Li; Ming Zhang; Zhijie Zhang; Tong Che (Metals)
Nano-sized tungsten exhibits superior properties due to its high-density grain boundaries’ strengthening. The high-quality nano-sized powder is essential for sintering nano-sized tungsten bulks through powder metallurgy techniques. In this study, nano-sized tungsten powder was successfully synthesized by mechanochemical methods using mixed WO3 and Mg powders. The effects of processing parameters on the morphology and microstructure of synthesized powder were thoroughly investigated. The results reveal that the thermite reaction of WO3 and Mg is almost complete after 5 min of ball milling at a speed of 300 rpm. The average grain size of the tungsten powder decreases with the increasing milling duration and speed. Optimal average grain size and purity were achieved at a milling speed of 300 rpm and a milling duration ranging from 30 to 120 min. Moreover, centrifugation sieving further reduces the average grain size of tungsten powder to 19.5 nm. In addition, the entire mechanochemical process can be divided into two stages: the reaction stage and the grain size refinement stage.